Perioperative COX2 and β‐adrenergic blockade improves biomarkers of tumor metastasis, immunity, and inflammation in colorectal cancer: A randomized controlled trial. Issue 17 (13th June 2020) - Haldar, Rita; Ricon‐Becker, Itay; Radin, Arielle; Gutman, Mordechai; Cole, Steve W.; Zmora, Oded; Ben‐Eliyahu, Shamgar
Abstract : Background: Preclinical studies have implicated excess release of catecholamines and prostaglandins in the mediation of prometastatic processes during surgical treatment of cancer. In this study, we tested the combined perioperative blockade of these pathways in patients with colorectal cancer (CRC). Methods: In a randomized, double‐blind, placebo‐controlled biomarker trial involving 34 patients, the β‐blocker propranolol and the COX2‐inhibitor etodolac were administered for 20 perioperative days, starting 5 days before surgery. Excised tumors were subjected to whole genome messenger RNA profiling and transcriptional control pathway analyses. Results: Drugs were well‐tolerated, with minor complications in both the treatment group and the placebo group. Treatment resulted in a significant improvement ( P  < .05) of tumor molecular markers of malignant and metastatic potential, including 1) reduced epithelial‐to‐mesenchymal transition, 2) reduced tumor infiltrating CD14 + monocytes and CD19 + B cells, and 3) increased tumor infiltrating CD56 + natural killer cells. Transcriptional activity analyses indicated a favorable drug impact on 12 of 19 a priori hypothesized CRC‐related transcription factors, including the GATA, STAT, and EGR families as well as the CREB family that mediates the gene regulatory impact of β‐adrenergic– and prostaglandin‐signaling. Alterations observed in these transcriptional activities were previously associated with improved long‐term clinical outcomes. Three‐year recurrence rates were assessed for long‐term safety analyses. An intent‐to‐treat analysis revealed that recurrence rates were 12.5% (2/16) in the treatment group and 33.3% (6/18) in the placebo group ( P  = .239), and in protocol‐compliant patients, recurrence rates were 0% (0/11) in the treatment group and 29.4% (5/17) in the placebo group ( P  = .054). Conclusions: The favorable biomarker impacts and clinical outcomes provide a rationale for future randomized placebo‐controlled trials in larger samples to assess the effects of perioperative propranolol/etodolac treatment on oncological clinical outcomes. Abstract : Simultaneous 20‐day perioperative inhibition of β‐adrenergic and COX2 signaling in patients with colorectal cancer has a favorable impact on tumor biomarkers associated with metastatic progression. Our results suggest scientific, medical, and safety justifications to conduct large‐scale clinical trials, assessing long‐term cancer outcomes.